Bilateral Chylothorax Post Blunt Trauma: A Case Report - Muhammad Waseem, Maryam Rafiq, M Haseeb Malik (Journal of Rawalpindi Medical College, 2021)
Introduction: Blunt trauma is a rare cause of chylothorax. In this study an uncommon case of traumatic chylothorax after blunt trauma is described along with treatment options. Report on a Case: A 50-year-old male was admitted to the hospital with sudden onset of shortness of breath for one day. He had a history of road traffic accident 2 days ago, in which he received a strong jerk while trying to avoid impact with the dashboard of the vehicle. He has no past medical history. On examination, He was fully conscious and oriented. Air entry on both sides of the chest was reduced. The x-ray of the chest revealed bilateral blunting of costo-phrenic angels due to pleural effusion. Pleural fluid was sent for biochemical, microbiological and histopathological analysis. Fluid Triglyceride and cholesterol levels were elevated. Culture and sensitivity were negative while cytopathological analysis revealed increased WBCs. CT scan of the chest did not reveal any malignancy or mediastinal lymph nodes. Bilateral Chest intubation was done to treat severe shortness of breath, that drained milky white fluid. The patient was observed without any particular treatment other than chest intubation. The patient responded well and was discharged uneventfully after five days. Conclusion: Despite its rarity, chylothorax can occur after blunt trauma. Diagnosis should be confirmed by laboratory testing. Conservative management with or without chest intubation is a common treatment option. Keywords: Blunt chest trauma, Chylothorax, Triglyceride.